Die amerikanische Verheissung Schweizer Aussenpolitik im Wirtschaftskrieg 1917/18 - Weber, Florian (Chronos Verlag, 2016)
Abstract in English* The promise of America Swiss foreign policy amidst the economic warfare of 1917-18 The book tells the dramatic history of the final two years of World War I, during which Switzerland was in between the fronts of the world powers. The surrounding struggle for global domination caused serious difficulties for the small state. Cut off from important food imports, resulting from the indiscriminate German submarine warfare, it turned for help to the USA. The pleas of a high-ranking "Swiss Mission" sent across the Atlantic were heeded: The USA supplied the landlocked country with grain thus averting famine. While America thus boosted its reputation, the German empire became more of a threat. Agitation increased when German agents were convicted in spy scandals and trials of bombers in Zurich. Despite German propaganda, the German empire was unable to maintain its influence in Switzerland. German diplomats, as representatives of the unpopular old order, were expelled from Switzerland when the Central Powers collapsed in the fall of 1918. The USA under President Woodrow Wilson was, in contrast, enthusiastically celebrated. This study, just barely one hundred years later, enables a new view of one of the most animated periods in Swiss history, offering an opportunity to reflect on the relation of this small country to the rest of the world.